Efficacy and Safety of Anlotinib in the Treatment of Small Cell Lung Cancer: A Real-World Observation Study - Yuan, Jing; Cheng, Feng; Xiao, Guodong; Wang, Xiaofeng; Fan, Huijie (Frontiers in Oncology, 2022)
Aims: This study aimed to observe the efficacy and safety of anlotinib in the treatment of small cell lung cancer (SCLC) in the real world, as first-line maintenance therapy, second-line, and above. Methods: Clinical data of 109 patients with SCLC treated with anlotinib and hospitalized at The First Affiliated Hospital of Zhengzhou University from June 2018 to June 2020 were retrospectively analyzed. Analysis of short-term efficacy and survival was performed, with p<0.05 being considered statistically significant. Results: The median progression-free survival (mPFS) of anlotinib monotherapy used as first-line maintenance treatment of SCLC was 6.3 months (11.7 months in the limited phase and 5.8 months in the extensive phase) and median overall survival (mOS) was 16.7 months (not reached in limited phase, 12.6 months in extensive phase). In second-line treatment, anlotinib with chemotherapy prolonged PFS and OS as compared to anlotinib monotherapy (p＜0.05). In third-line and above treatment, there was no improvement in mPFS with the chemotherapy combination regimen compared to anlotinib monotherapy (3.6 months vs. 3.8 months, p=0.398), with a trend toward impaired mOS (8.5 months vs. not achieved, p=0.060). Univariate analyses and multivariate analyses revealed that Eastern Cooperative Oncology Group performance status and liver metastases were independent prognostic factors affecting PFS and OS. No new anlotinib-related adverse reactions were identified. Conclusion: Anlotinib was effective for first-line maintenance and second-line treatment, and the chemotherapy combination regimen was superior to monotherapy when applied as second-line treatment. However, this trend was not observed in third-line and above therapy.